Semiotika Pada Tanda Dilarang Berpacaran (Studi di Tiga Taman Kota: Taman Cerdas, Taman Samarendah, dan Taman Islamic) - Afita Nur Hayati (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2021)
This article aims to highlight denotation and conotation meaning of sign of dilarang berpacaran that is on Samarinda city parks. City parks that is taken are public sphere, iconic, dan near from another public spaces. Analysis of semiotics from Roland Barthes is used as method. Datas taken through interview with city parks visitors, observations and secondary sources with results : 1) city parks as a form of ruang terbuka hijau (green open space) have two functions, ecology and social, 2) sign of dilarang berpacaran is normative semiotics and cultural semiotics.